Using Picture Media to Improve Learning Storytelling Skills in Elementary School Students - Laukhatul Jannah (Jurnal Pendidikan Profesi Guru, 2023)
The basis of this research is that the learning outcomes of students' storytelling abilities in Indonesian learning are very low. The purpose of this research is to improve the storytelling skills of elementary school students using picture learning media. This research is a Classroom Action Research conducted through two cycles. In this study the subjects were 15 second grade of elementary school students with details of 7 male and 8 female. Data collection is done by observation, test and documentation. The data obtained in this study were analyzed using descriptive statistical techniques. This study shows the results that the storytelling skills of elementary school students can be improved by using picture media. This is evidenced by the pre-cycle results which show that only 33.33% of students' storytelling skills are in the complete category. In cycle I there was an increase in the mastery of students' storytelling skills to 60%. Furthermore, in second cycle there was an increase in students' storytelling skills to 100% complete. From these results it was concluded that the storytelling ability of elementary school students could be improved by image media in Indonesian learning.